1993
DOI: 10.1021/ic00078a005
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transfer kinetics of copper(II/I) macrocyclic tetrathiaether complexes. Influence of ring size upon gated behavior

Abstract: The values of the electron self-exchange rate constants, kl I (~~) , for the copper(II/I) complexes formed with the cyclic tetrathiaethers [ 131aneS4 and [ 1 51aneS4 have been determined using IH-NMR line-broadening measurements in D20 at several different temperatures to yield the following results for 25 OC, corrected to p = 0.1 M (NO3-): for CuIV1 ([13]aneS4), kll(ex) = 3.2 X 105 M-1 s-1, AH* = 10 f 1 kJ mol-', AS* = -106 f 7 J K-1 mol-1; for CuII/1- ([15]aneS,), kll(cx) = 1.2 X 104 M-1 s-1, AH* = 21 f 1 kJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 2 publications
2
55
4
Order By: Relevance
“…A closely related ligand, designated as [15]aneNS 4 ( Figure 11), in which one of the sulfur donor atoms was replaced by an amine nitrogen donor atom, yielded k 11 ) (1-2) × 10 5 M -1 s -1 by NMR, and this value was shown to be consistent with k 11 values generated from both Cu II L reduction and Cu I L oxidation reactions. 151 The Cu II/I ([13]aneS 4 ) system, which was cited earlier with the macrocyclic polythiaether complexes, also yielded a large k 11 value of 3 × 10 5 M -1 s -1 as determined by NMR with corroborative k 11 values being generated from reduction reactions of Cu II L. 133 An examination of the crystal structures shows that this system is structurally similar to the Cu II/I ([15]aneS 5 ) system in that both Cu II ( [15]aneS 5 ) 169 and Cu II ( [13]aneS 4 ) 170 are square pyramidal, the latter having a water molecule occupying the apical site. Upon reduction of the former complex, one of the Cu-S bonds in the plane dissociates to generate a tetrahedral complex in which none of the donor atoms is required to change the orientation of its lone electron pair.…”
Section: Copper(ii/i) Systems Exhibiting Rapid Electron Exchangementioning
confidence: 63%
See 2 more Smart Citations
“…A closely related ligand, designated as [15]aneNS 4 ( Figure 11), in which one of the sulfur donor atoms was replaced by an amine nitrogen donor atom, yielded k 11 ) (1-2) × 10 5 M -1 s -1 by NMR, and this value was shown to be consistent with k 11 values generated from both Cu II L reduction and Cu I L oxidation reactions. 151 The Cu II/I ([13]aneS 4 ) system, which was cited earlier with the macrocyclic polythiaether complexes, also yielded a large k 11 value of 3 × 10 5 M -1 s -1 as determined by NMR with corroborative k 11 values being generated from reduction reactions of Cu II L. 133 An examination of the crystal structures shows that this system is structurally similar to the Cu II/I ([15]aneS 5 ) system in that both Cu II ( [15]aneS 5 ) 169 and Cu II ( [13]aneS 4 ) 170 are square pyramidal, the latter having a water molecule occupying the apical site. Upon reduction of the former complex, one of the Cu-S bonds in the plane dissociates to generate a tetrahedral complex in which none of the donor atoms is required to change the orientation of its lone electron pair.…”
Section: Copper(ii/i) Systems Exhibiting Rapid Electron Exchangementioning
confidence: 63%
“…56,133,134 The electron-transfer kinetics for each of these five systems were measured with a total of four reductants and four oxidants, and independent k 11 values were also obtained from NMR line broadening measurements. 56,133,134 In all five systems, the calculated k 11(Red) values were in close agreement with the corresponding values obtained by NMR (Table 7). This observation was in sharp contrast to the original suggestion by Lee and Anson 39 that the k 11 value for Cu(II/I) systems, as determined directly without invoking eq 14, should be the geometric mean of k 11(Red) and k 11(Ox) (see section 4.3).…”
Section: Thiaether Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the cross-reaction rate constant values (k 12 and k 21 ) in Table 5 were used to generate values for the apparent electron self-exchange rate constant, k 11 , by means of the Marcus cross relationship: 59 where k 22 represents the self-exchange rate constant for the counter reagent; K 12 and K 21 represent the equilibrium constants for the overall reactions as calculated from the redox potentials; f 12 and f 21 represent non-linear terms calculated from As noted in the Introduction, our earlier studies on Cu II/I -( [14]aneS 4 -a) 1 and related systems, 2-7, 60 have shown that their electron-transfer kinetic behavior is consistent with a mechanistic scheme in which a major conformational change and the electron-transfer step occur sequentially rather than concertedly to yield at least two competing pathways, A and B, (Fig. 1).…”
Section: Electron Self-exchange Rate Constantsmentioning
confidence: 99%
“…11, 20 Reduction of these complexes then involves the rupture of a basal Cu-S bond without the requirement of either donor atom inversion or the rupture of a solvent bond, and the electron-transfer kinetics tend to be relatively fast. 6,11 In fact, the copper system involving a substituted 12-membered macrocycle, oxathiane- [12]aneS 4 , has yielded the largest self-exchange rate constant yet recorded for an inorganic Cu(II/I) system. 11 Interestingly, expansion of the macrocyclic ring to 15-members incorporating five thioether sulfurs or four sulfur and one nitrogen donor atoms has also led to faster electron transfer.…”
Section: Introductionmentioning
confidence: 99%